2013
DOI: 10.1242/dev.091355
|View full text |Cite
|
Sign up to set email alerts
|

ASCL1 reprograms mouse Müller glia into neurogenic retinal progenitors

Abstract: SUMMARYNon-mammalian vertebrates have a robust ability to regenerate injured retinal neurons from Müller glia (MG) that activate the gene encoding the proneural factor Achaete-scute homolog 1 (Ascl1; also known as Mash1 in mammals) and de-differentiate into progenitor cells. By contrast, mammalian MG have a limited regenerative response and fail to upregulate Ascl1 after injury. To test whether ASCL1 could restore neurogenic potential to mammalian MG, we overexpressed ASCL1 in dissociated mouse MG cultures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
224
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(245 citation statements)
references
References 67 publications
20
224
1
Order By: Relevance
“…Activated Notch signaling and upregulation of Ascl1a are known to stimulate the formation of MGPCs in the retina (Fausett et al, 2008;Ghai et al, 2010;Hayes et al, 2007;Pollak et al, 2013). Consistent with previous reports (Hayes et al, 2007), we found increases in retinal levels of chick Delta1, Dll4, Jag (not shown), Notch1, Hes5 and Ascl1a (Fig.…”
Section: Müller Glia (Data Not Shown) By Contrast Injections Of Dex Orsupporting
confidence: 92%
“…Activated Notch signaling and upregulation of Ascl1a are known to stimulate the formation of MGPCs in the retina (Fausett et al, 2008;Ghai et al, 2010;Hayes et al, 2007;Pollak et al, 2013). Consistent with previous reports (Hayes et al, 2007), we found increases in retinal levels of chick Delta1, Dll4, Jag (not shown), Notch1, Hes5 and Ascl1a (Fig.…”
Section: Müller Glia (Data Not Shown) By Contrast Injections Of Dex Orsupporting
confidence: 92%
“…One candidate for this repression, let-7, appears to inhibit regeneration in both zebrafish and Caenorhabditis elegans (14,30). Interestingly, Ascl1a inhibits let-7 expression during zebrafish MG reprogramming (14), and its overexpression in postnatal mouse MG enhanced their reprogramming (31). We suspect that this latter effect is mediated by inhibition of let-7 and hypothesize that let-7 is a key factor contributing to the limited regenerative potential of mammalian MG.…”
Section: Discussionmentioning
confidence: 93%
“…S4). Proneural/retinal markers NEU-ROD1, responsible for the development of PRs and amacrines [48], and ASCL1 (MASH1) [49], which determine competence-restricted progenitor lineage in the retina [50], demonstrated very high expression reaching a peak at 4 weeks (377.3 -5.5 and 134.2 -12.5, respectively). The CHX10 marker of multipotential retinal progenitors and bipolar cell fate [51,52] Table S3).…”
Section: Resultsmentioning
confidence: 99%